2019
DOI: 10.1002/jbt.22422
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chemokines in macrophage polarization and downregulation of NFκB in aorta allow macrophage polarization by diosgenin in atherosclerosis

Abstract: M1 macrophages serve one edge as proinflammatory and M2 macrophages serve the other edge as an anti-inflammatory macrophage. It appears that a related "switch" in macrophage morphology may also happen in the course of atherosclerosis, which has not yet been elucidated. An atherogenic diet (AD) was given to rats, and induction of macrophage differentiation and the nuclear localization of nuclear factor-kappa B (NFκB) were investigated by Western blot and immunofluorescence. Chemokines were analyzed using an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…As reported by Binesh et al [ 84 ], notch intracellular domain (NICD) could be regulated by NF- κ B inhibition, which in turn down macrophage differentiation afterward. He further proved [ 85 ] that diosgenin regulates the differentiation of monocyte not by inhibiting its differentiation to macrophage but inducing its differentiation to M2 macrophage, thus, preventing the promotion of atherosclerosis. In addition, HIF [ 79 ] is reported as a crucial factor which could mediate the formation of foam cells by regulating efflux pathways in macrophages through the NF- κ B signaling pathway.…”
Section: Cytokines/receptors and Other Biochemical Factors Involved In Monocyte Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by Binesh et al [ 84 ], notch intracellular domain (NICD) could be regulated by NF- κ B inhibition, which in turn down macrophage differentiation afterward. He further proved [ 85 ] that diosgenin regulates the differentiation of monocyte not by inhibiting its differentiation to macrophage but inducing its differentiation to M2 macrophage, thus, preventing the promotion of atherosclerosis. In addition, HIF [ 79 ] is reported as a crucial factor which could mediate the formation of foam cells by regulating efflux pathways in macrophages through the NF- κ B signaling pathway.…”
Section: Cytokines/receptors and Other Biochemical Factors Involved In Monocyte Migrationmentioning
confidence: 99%
“…Earlier studies demonstrated that oxidized LDL (oxLDL) could promote the differentiation of monocyte [ 84 , 85 ], the chemotaxis of macrophages [ 87 ], but inhibit their egress [ 88 , 89 ]. Recent studies showed that oxLDL mainly induces monocytes differentiated to M1 macrophage, which are proinflammatory [ 90 ] and assumed to have lower migration ability [ 91 ].…”
Section: Cytokines/receptors and Other Biochemical Factors Involved In Monocyte Migrationmentioning
confidence: 99%
“…Macrophages are mainly divided into two different subtypes: M1-type macrophages are mainly found in unstable plaques, whereas M2-type macrophages are predominantly found in stable plaque tissue (5,6). During the development of the disease, various external factors affect macrophages, and depending on the M1/M2 polarization status, the corresponding inflammatory process is highly different (5,7). Binesh et al (7) found that pro-inflammatory macrophages (M1-type) were expressed in atherogenic diet-induced aorta, while anti-inflammatory macrophages (M2-type) were expressed in diosgenin-treated aorta.…”
Section: Introductionmentioning
confidence: 99%
“…During the development of the disease, various external factors affect macrophages, and depending on the M1/M2 polarization status, the corresponding inflammatory process is highly different (5,7). Binesh et al (7) found that pro-inflammatory macrophages (M1-type) were expressed in atherogenic diet-induced aorta, while anti-inflammatory macrophages (M2-type) were expressed in diosgenin-treated aorta. Therefore, improving the condition of the disease by regulating the polarization of M1-type macrophages may be one mechanism to control immune regulation in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…CVD claims more lives than all forms of cancer deaths combined. Cardiovascular diseases are the first leading cause of death and morbidity in developed countries (Gaziano et al 2010;Binesh et al 2020a;Binesh et al 2020b). The use of animal models has helped to increase our understanding, opening up new tools that are concentrated on strengthening the diagnosis and treatment of these pathologies.…”
Section: Introductionmentioning
confidence: 99%